Severity and treatment of cognitive impairment - Yu. A. Starchina; V. V. Zakharov (Неврология, нейропсихиатрия, психосоматика, 2021)
With an increase in life expectancy in the population, the proportion of people with cognitive impairment (CI) increases. Modern neurology focuses on the milder forms of CI: moderate, mild, and subjective CI, which are more promising in terms of successful treatment and slowing down their progression. Age is the leading risk factor for CI, the prevalence of which in the general population of people aged over 65 years reaches 10–15%. The primary role in CI development is played by Alzheimer's disease, cerebrovascular diseases, mixed vascular-neurodegenerative process, and other types of neurodegenerative diseases, and all of them share some pathophysiological mechanisms. Correction of vascular risk factors plays a leading role in the treatment of pre-dementia stages of CI. The possibilities of using nimodipine in the therapy of CI are analyzed.